Lembaga Olah Seni Budaya Jambi Kota Seberang Mengenal Kompangan Dan Hadrah Sebagai Seni Tradisional Melayu Jambi 1995-2017 - Siti Heidi Karmela; Ferry Yanto; Malynda Ayu Aprilia (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This research is a historical study with the theme of cultural history, with the object of research being the Kompangan Group and the Hadrah Group belonging to the Jambi seberang cultural arts institute in Jelmu village, Kampung Tengah Sekoja district. The main research problem is about “Kompangan and Hadrah Group Managed by LOSBJKS in Jelmu Village Since 1995 – 2017”, with two formulation of the problem proposed, namely; why LOSBJKS as an art institution can advance and develop the arts of Kompangan and Hadrah especially in Jelmu village and generally in the Sekoja area, and how LOSBJKS in preserving the values contained in the art of Kompangan and Hadrah as Jambi Malay traditional arts. The research objective is to explain the development of the Kompangan and Hadrah Groups belonging LOSBJKS which are the pioneers for the emergence of other traditional art groups especially in Jelmu village and generally in Sekoja area. In addition, it can also describe the roles and contributions of the board and members who are members of LOSBJKS to preserve the arts of Kompangan and Hadrah as traditional Jambi Malay arts. The research method used is the historical method which is method in historical research, where according to Kuntowijoyo the method starts from the heuristic, criticism, interpretation, and historiography. The findings show that there are change and developments from LOSBJKS, namely, first it can be seen from the name change from Riyadusholihin to LOSBJKS. Second, it is seen in the wider area of origin of permanent and non-permanent members. Third, in the terms of musical instruments, fourth, namely the costumes used especially the members of the Hadrah Group. Fifth, there was a change in the Kompangan technique (straight and circular patterns), if previously it was more characteristic of the Palembang (irregular) hitting technique, it had changed to Jambi striking technique that was more polite and neat. Sixth, in therm of singing there has also been a change, namely generally prayer and Malay songs, but at festivals sometimes there are also local songs so that they are not monoton.